(untitled) (Sahel Journal of Life Sciences FUDMA, 2025)
Malaria is a major parasitic disease in the world, especially in Africa and antimalarial drug resistance has emerged as one of the greatest challenges facing malaria control today. This study investigated the antiplasmodial effects of methanol leaf extract of Azadirachta indica, Senna occidentalis, Senna siamea, and standard antimalarial drugs. Plant samples were collected and screened for qualitative phytochemicals. Plasmodium falciparum was obtained from symptomatic patients, confirmed using RDTs, and cultured in RPMI 1640 media supplement with 10% human AB+ serum. Varying concentrations of the extracts, such as 100, 200, and up to 1000 Âµg/ml were prepared. The results of phytochemical screening indicated that A. indica, S. occidentalis, and S. siamea contain Alkaloids, Flavonoids, Saponins, Saponins glycosides, Steroids, and Terpenoids. Methanol plant extracts showed that Combination therapy exhibited the highest growth inhibition, achieving 98.48% effectiveness at 400 Âµg/ml. The acute toxicity studies in rats showed no significant adverse effects at doses up to 3000 mg/kg. These findings highlight the pharmacological potential and safety of these plant extracts, supporting further investigations for malaria treatment.